2020
DOI: 10.2196/19044
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and Design of the Women’s Health And Daily Experiences Project: Protocol for an Ecological Momentary Assessment Study to Identify Real-Time Predictors of Midlife Women’s Physical Activity

Abstract: Background Midlife women are at an elevated risk for cardiovascular disease (CVD) and associated mortality. Those who have additional risk conditions such as obesity or hypertension report specific barriers to engaging in cardioprotective behaviors such as physical activity (PA). Considerable effort has been devoted to understanding PA determinants and designing interventions for midlife women, although with suboptimal success, as increasing PA could meaningfully attenuate CVD risk. An updated appr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 136 publications
0
6
0
Order By: Relevance
“…Finally, BCTs and intervention features that were described as activating BCTs were extracted. An initial set of BCTs were selected for extraction based on the authors' familiarity with physical activity intervention research (specific to women in midlife and more broadly; Arigo, 2015 ; Butryn et al, 2016 ; Arigo et al, 2020a , b ). These BCTs included the following [with Michie et al ( 2013 ) associated numeric codes]: goal setting (proximal behavior [1.1] and/or distal outcome [1.3]), self-monitoring (proximal behavior [2.3] and/or distal outcome [2.4]), providing feedback (2.2), problem-solving and/or planning (1.4 and 1.2, respectively), social support (3.1–3.3), social comparison (6.2), and behavioral modeling (6.1).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, BCTs and intervention features that were described as activating BCTs were extracted. An initial set of BCTs were selected for extraction based on the authors' familiarity with physical activity intervention research (specific to women in midlife and more broadly; Arigo, 2015 ; Butryn et al, 2016 ; Arigo et al, 2020a , b ). These BCTs included the following [with Michie et al ( 2013 ) associated numeric codes]: goal setting (proximal behavior [1.1] and/or distal outcome [1.3]), self-monitoring (proximal behavior [2.3] and/or distal outcome [2.4]), providing feedback (2.2), problem-solving and/or planning (1.4 and 1.2, respectively), social support (3.1–3.3), social comparison (6.2), and behavioral modeling (6.1).…”
Section: Methodsmentioning
confidence: 99%
“…Despite these delays, this study had several strengths, including a base of foundational work with the population of interest [ 32 , 37 , 60 , 61 , 69 ], adherence to widely recommended UCD principles [ 51 , 73 ], emphasis on recruiting women from racial or ethnic minority backgrounds to maximize diversity in small samples, and collaboration between flexible researchers who are committed to the project. This process also benefited from multiple phases of internal testing, including a range of testers who were familiar with and those who were naïve to the web application specifications and phases of both positive and negative testing.…”
Section: Discussionmentioning
confidence: 99%
“…Although we considered a stand-alone mobile app as the outcome, we selected a web application owing to its versatility and ease of access across devices and platforms. During this time, the first author built on her previous studies with the population of interest [ 37 , 39 , 59 ] by conducting additional observational and qualitative studies [ 32 , 33 , 60 , 61 ] and collecting preliminary data to assess their needs and preferences. Insights from previous studies, discussions between investigators, and new participant responses informed the refinement of the goals of the new tool.…”
Section: Methodsmentioning
confidence: 99%
“…For example, identifying women for whom certain social perceptions are associated with low engagement in physical activity could help to target appropriate interventions toward this subgroup of women. In contrast, identifying when or in what contexts certain social perceptions are associated with decreases in women's physical activity could help to identify the appropriate timing or circumstances for exposure to intervention content or reminders about using specific behavioral skills (31). Previous work has shown that intensive assessment (specifically, EMA) is feasible and acceptable among midlife women for capturing self-perceptions [e.g., of self-efficacy or physical activity engagement (32)].…”
Section: Case Example: Intensive Assessment Among Midlife Women With Elevated Risk For Cardiovascular Disease (Cvd)mentioning
confidence: 99%
“…With these points in mind, the present series of studies was designed to inform refinements to intensive assessment items for use with midlife women experiencing elevated CVD risk. The ultimate goal of this work is to investigate between-and within-person relations between social perceptions and physical activity in this population, using an EMA design (31). In Study 1, we used EMA to pilot items with this population for seven days and collected feedback about their experiences with these items.…”
Section: Aims Of the Present Researchmentioning
confidence: 99%